Functional MRI mapping neuronal inhibition and excitation at columnar level in human visual cortex - Zhang, Nanyin (2010)
The capability of non-invasively mapping neuronal excitation and inhibition at the columnar level in human is vital in revealing fundamental mechanisms of brain functions. Here, we show that it is feasible to simultaneously map inhibited and excited ocular dominance columns (ODCs) in human primary visual cortex by combining high-resolution fMRI with the mechanism of binocular inhibitory interaction induced by paired monocular stimuli separated by a desired time delay. This method is based on spatial differentiation of fMRI signal responses between inhibited and excited ODCs that can be controlled by paired monocular stimuli. The feasibility and reproducibility for mapping both inhibited and excited ODCs have been examined. The results conclude that fMRI is capable of non-invasively mapping both excitatory and inhibitory neuronal processing at the columnar level in the human brain. This capability should be essential in studying the neural circuitry and brain function at the level of elementary cortical processing unit.